2009
DOI: 10.1186/1472-6947-9-31
|View full text |Cite
|
Sign up to set email alerts
|

Security and privacy requirements for a multi-institutional cancer research data grid: an interview-based study

Abstract: BackgroundData protection is important for all information systems that deal with human-subjects data. Grid-based systems – such as the cancer Biomedical Informatics Grid (caBIG) – seek to develop new mechanisms to facilitate real-time federation of cancer-relevant data sources, including sources protected under a variety of regulatory laws, such as HIPAA and 21CFR11. These systems embody new models for data sharing, and hence pose new challenges to the regulatory community, and to those who would develop or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Policy issues involved with real-time information exchange in support of biomedical research were studied by researchers associated with the cancer Biomedical Informatics Grid (caBIG). In an effort to understand the regulatory challenges posed by the real-time federation of clinical data for caBIG, researchers interviewed decision-makers from participating research centers and identified several policy concerns grouped around a number of broad themes, including governance, legal and financial, technical infrastructure, trust, auditing, risk management, and patient consent [15]. We have chosen these themes as initial focus areas for our model.…”
Section: Methodsmentioning
confidence: 99%
“…Policy issues involved with real-time information exchange in support of biomedical research were studied by researchers associated with the cancer Biomedical Informatics Grid (caBIG). In an effort to understand the regulatory challenges posed by the real-time federation of clinical data for caBIG, researchers interviewed decision-makers from participating research centers and identified several policy concerns grouped around a number of broad themes, including governance, legal and financial, technical infrastructure, trust, auditing, risk management, and patient consent [15]. We have chosen these themes as initial focus areas for our model.…”
Section: Methodsmentioning
confidence: 99%
“…A further, more detailed treatment of the topic of governance in federations involving academic medical centers can be found in Manion et al (2009) and Weems et al (2007).…”
Section: Issues Of Incorporation and Governancementioning
confidence: 98%
“…Our approach is based on earlier qualitative research on the complex regulatory requirements of biomedical data grids (19). Each institution obtains an exempt approval from each institution’s IRB to create and maintain its TIES node.…”
Section: Ensuring Regulatory Compliancementioning
confidence: 99%